Cancer prevention and therapy through the modulation of transcription factors by bioactive natural compounds - Shanmugam, M.; Lee, J.; Chai, E.; Kanchi, M.; Kar, S.; Arfuso, Frank; Dharmarajan, A.; Kumar, A.; Ramar, P.; Looi, C.; Mustafa, M.; Tergaonkar, V.; et al. (2015)
The association between chronic inflammation and cancer development has been well documented. One of the major obstacles in cancer treatment is the persistent autocrine and paracrine activation of pro-inflammatory transcription factors such as nuclear factor-?B, signal transducer and activator of transcription 3, activator protein 1, fork head box protein M1, and hypoxia-inducible factor 1a in a wide variety of tumor cell lines and patient specimens. This, in turn, leads to an accelerated production of cellular adhesion molecules, inflammatory cytokines, chemokines, anti-apoptotic molecules, and inducible nitric oxide synthase. Numerous medicinal plant-derived compounds have made a tremendous impact in drug discovery research endeavors, and have been reported to modulate the activation of diverse oncogenic transcription factors in various tumor models. Moreover, novel therapeutic combinations of standard chemotherapeutic drugs with these agents have significantly improved patient survival by making cancer cells more susceptible to chemotherapy and radiotherapy. In this review, we critically analyze the existing literature on the modulation of diverse transcription factors by various natural compounds and provide views on new directions for accelerating the discovery of novel drug candidates derived from Mother Nature.